Coroutine Sequencing in BETA - Kristensen, Bent Bruun; Møller-Pedersen, Birger; Madsen, Ole Lehrmann; Nygaard, Kristen (DAIMI Report Series, 1987)
In the object-oriented perspective a program execution is viewed as a physical model of some real or imaginary part of the world. A programming language supporting the object-oriented perspective must therefore contain comprehensive facilities for modelling phenomena and concepts from the application domain. In object-oriented programming objects model physical material and classes model concepts. By means of subclassing and virtual attributes it is possible to model a hierarchical classification of objects. Many applications in the real world consist of objects carrying out sequential processes. Coroutines may be used for modelling objects that alternate between a number of sequential processes. This paper describes coroutines in BETA.